Guides within the circle : aboriginal counsellors’ experiences with aboriginal families affected by fetal alcohol syndrome ... - Robert, Renee (University of British Columbia, 2009)
This research explores the experiences of six Aboriginal counsellors who provide services to Aboriginal families affected by Fetal Alcohol Syndrome. The focus of this research is on the experience and skill which First Nations counsellors employ with Aboriginal families affected by the disease. As well, literature on Fetal Alcohol Syndrome and counsellors' prevention and intervention strategies are explored. The current F.A.S. literature and Canadian Aboriginal history explored in the literature review roots the counsellors' present day experiences in the "Constructions" chapter. Within this qualitative research project, transcribed in-depth interviews of six Aboriginal counsellors' experiential knowledge were explored through the use of narrative analysis techniques. Analysis of the data revealed various themes. The themes indicated that Aboriginal counsellors' concerns regarding F.A.S. included: Aboriginal identity (for themselves and their clients); counselling work issues; as well as acknowledgement of ...